Ocular Image and Haemodynamic Features Associated with Different Gradings of Ipsilateral Internal Carotid Artery Stenosis - Hui Wang; Hongyang Li; Xiaojie Zhang; Lanyan Qiu; Zhenchang Wang; Yanling Wang (Journal of Ophthalmology)
Objectives. To analyse the changes of ocular haemodynamics and morphology in Chinese patients with internal carotid artery (ICA) stenosis in the current study. Methods. A retrospective case-control study was conducted with 219 patients. The haemodynamic characteristics, the calibre of retinal vessels, and the subfoveal choroidal thickness (SFChT) were compared. We analysed the correlations with the degree of ipsilateral ICA stenosis. Results. There were no significant differences among the groups in the central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE), and AVR (p=0.073, p=0.188, and p=0.738, resp.). The peak systolic velocity (PSV) and end diastolic velocity (EDV) in the central retinal artery (CRA) and the posterior ciliary artery (PCA) were significantly lower than normal eyes (p<0.001). The outer retinal layer thickness and SFChT values of the ICA stenosis groups were significantly lower than normal eyes (p=0.030 and p<0.001, resp.). Conclusion. The PSV and EDV in CRA and PCA and the SFChT and outer retinal layer thickness of ICA eyes were significantly lower than normal eyes. ICA stenosis may impact choroidal haemodynamics, and decreased choroidal circulation might affect the discordance of the SFChT and the outer retinal layer thickness.